Students' mathematics problem-solving skills through the application of Problem-Based Learning model - Suryani, I; Maidiyah, E; Salasi; Mardhiah, MZ (Journal of physics. Conference series, 2020)
Education aims to foster a variety of potential which exists in human, including the potential to solve any problems, involving solving mathematical problems. This study aimed to describe students' problem-solving skills during mathematics learning about social arithmetic through Problem-Based Learning (PBL) model. The subjects of this research were 32 Year 7 students in Banda Aceh. This study used a qualitative descriptive approach. Data collection was conducted by problem-solving skills test and interview. The interview data were analysed descriptively, while the data of the test results were analysed based on the assessment guideline of students' problem-solving skills. It was found that students' mathematical problem-solving skills through PBL model were already classified as good. High-achieving students of problem-solving skills solved the problem by understanding the problem, planning the solution, doing the solution and rechecking it. Middle-achieving students of problem-solving skills solved the problem by understanding the problem, planning the solution and doing the solution without rechecking it so they get incorrect results. Low-achieving students of problem-solving skills solved the problem by understanding the problem and planning the solution, yet they presented the incorrect solution and did not recheck it. PBL model can be used to improve students' problem-solving abilities.